PRICE DISPARITIES IN GICs, DOES IT INFLUENCE THE SURFACE CHARACTERIZATION? - Muhammad Dian Firdausy; Eko Hadianto; Sandy Christiono (FKG Unlam, 2022)
Background: Glass ionomer cement (GICs) has become a common restorative material in dental practice. Therefore, there are so many GIC's brands can be found in the market with tremendous price disparities GIC brands can be found in the market with huge price disparity; Price of one brand can be up to tenfold than the others. For the cost-efficiency reason, many clinicians prefer the more economical. Therefore, questions arise from the clinician, does it influence the clinical performance. Method: Six cylindrical specimens (10mm x 2mm) from four GIC brands (Fuji IX, FXUltra, GlassyCem and Sangchi) were made based on the respective factory instructions and stored for 24 hours until the final setting reached. Micro Vickers hardness tester (Shimadzu) and Surface roughness tester were used as surface characterizations measurement. Collected data were analyzed statistically. Results: Kruskal-Wallis and Mann-Whitney analysis showed that Fuji IX and FXUltra significantly (p<0.05) higher surface hardness (68.47 and 63.29 VHN respectively) compared to GlassyCem and Sangchi (38.53 and 36.70 VHN). While for surface roughness measurement, Fuji IX has the highest surface roughness, 7.22 µm (p<0.05). GIC’s clinical performance is affected by composition and powder-liquid ratio. Strontium in Fuji IX could increase surface hardness. The high powder-liquid ratio in Fuji IX and FXUltra improve its clinical performance compared to the other group. Conclusion: The more expensive GIC (Fuji IX and FX ultra) had better surface hardness with a slight difference in surface roughness. Therefore, clinicians should choose GIC based on cost-efficiency without ignoring clinical performance.